Pengembangan Media Pembelajaran Berbasis Aplikasi Android Menggunakan iSpring Dan APK Builder Pada Mata Pelajaran IPAS Kelas V SD Kurikulum Merdeka - Metodius Ady Setiawan Ady Setiawan (Departement of Mathematics Education, 2024)
This research aims to produce learning media based on Android applications. This Android application-based learning media is used by students on their personal devices by installing it. The research method used is Research and Development research, with the ADDIE model which has been adapted to research needs, so that researchers carry out analysis, design, development, and implementation steps. At the analysis stage, the researcher conducted interviews to see product needs, then at the design stage the researcher designed and designed Android application-based learning media in accordance with the needs analysis, then at the development stage, the researcher conducted trials with two experts, namely material, and media experts. Next the trial stage, each stage goes through a revision process according to suggestions from media experts and material experts. This research is limited to reach the implementation stage for users. A total of 15 students tested Android application-based learning media to see students' responses to the media used. Based on trials by material expert, media expert and users, a conclusion can be drawn that this Android application-based learning media is very suitable for use by users.